2022
DOI: 10.9734/jamcs/2022/v37i230433
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting of Road Traffic Flow Based on Harris Hawk Optimization and XGBoost

Abstract: With the development of society and economy, people's living standards are improving day by day. The number of private cars is increasing, and the problem of urban traffic congestion is becoming more and more serious. Short-term traffic flow prediction is crucial to assist intelligent transportation system decision-making, solve congestion problems, and improve road capacity. In order to effectively improve the prediction accuracy and improve the generalization performance of the model, this paper combines ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…They formed an integrated Bayesian model using the results of SWAT-VSA, ANN, and ARMA [11]; Jiayue Gu et al proposed an integrated learning model with KNN, XGB, SVR, and ANN as the base models. They used this model to predict monthly rainfall and finally obtained the prediction results with high accuracy [12]; Longfeng Zhang et al proposed a model combining the Harris Hawk optimization algorithm with the XGBoost model and predicted the short-term traffic flow, and the results showed that the accuracy and stability of the model were more significantly improved [13].…”
Section: Related Workmentioning
confidence: 99%
“…They formed an integrated Bayesian model using the results of SWAT-VSA, ANN, and ARMA [11]; Jiayue Gu et al proposed an integrated learning model with KNN, XGB, SVR, and ANN as the base models. They used this model to predict monthly rainfall and finally obtained the prediction results with high accuracy [12]; Longfeng Zhang et al proposed a model combining the Harris Hawk optimization algorithm with the XGBoost model and predicted the short-term traffic flow, and the results showed that the accuracy and stability of the model were more significantly improved [13].…”
Section: Related Workmentioning
confidence: 99%